Striped Lynx Spider Oxyopes salticus (Hentz 1845) (Arachnida: Araneae: Oxyopidae) - Laurel B. Lietzenmayer; Ronald D Cave; Lisa A Taylor (EDIS)
The striped lynx spider, Oxyopes salticus (Hentz), is a small, spiny-legged spider and generalist predator that feeds on a wide variety of insect prey, including several economically important insect pests. This lynx spider species is one of the most abundant beneficial spider species in gardens, yards, and agricultural fields throughout North America. https://edis.ifas.ufl.edu/in1259